Systematic Literature Review: Effectiveness of Insulin Combination Therapy with Glucagon-Like Peptide-1 (GLP-1) Incretin-Based Therapy in Patients with Type 2 Diabetes Mellitus - Sibarani, Benly Levi Andreas; Utami, Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Diabetes mellitus remains an evolving metabolic and endocrine disease. Effective pharmacological management of type 2 DM is still a global concern. Insulin therapy often causes side effects of hypoglycemia, so other therapies are expected to be combined with insulin. The literature reviewed in this review used two databases, PubMed and Cochrane, based on objectives, clinical keywords, and choice of articles according to predetermined inclusion and exclusion criteria. The methodology was a systematic approach involving identification, analysis, synthesis, evaluation, and comparison of relevant literature. A total of two results were obtained showing that the composite of insulin-based therapy and GLP-1 therapy in patients with type 2 DM provides effective results to control the levels of blood sugar in type 2 DM patients.